Normalização de descrição arquivística aplicada no fundo documental da secretaria de cultura do município de londrina - Dos Santos Costa, Eliandro; De Carvalho Madio, Telma Campanha [UNESP] (My University, 2017)
This paper aims to describe the results of a case study held at Secretaria de Cultura do Municipio de Londrina, an organ linked to the City Hall administration de Londrina. It has been developed with the support of the ICA-AtoM software as a resource for the application of the rules of archival description of the agency producing archival documents. For the purposes of their application, the documents were archived in the Patrimony Architectural and Historic Registry and in a documentary Series Architectural Records. For these archival descriptions, the following standards were used, respectively: NOBRADE and ODA, ISAAR-CPF, ISDF. Bibliographic, documentary, exploratory and applied and qualitative research was also adopted. Its results were not found in any ICA-AtoM Web Portal. This descriptive practice fostered a contribution to the area of archiving, where it can help local citizens and other interested publics to gain greater access to the archival record and history of the region, in this case, to the Buildings and historical monuments of the city.
Application of the ica-atom in the archival description of the documentary fund of the department of culture of the city of Londrina
Keywords: Archival description; Archivistic description standart; Archivology; ICAAtoM